2017
DOI: 10.1016/j.bpj.2016.11.2181
|View full text |Cite
|
Sign up to set email alerts
|

Electrically Dormant Sinoatrial Nodal Cells (SANC) are Awakened by Increased Camp-Dependent Phosphorylation of Coupled-Clock Proteins

Abstract: Regular exercise-training is known to reduce the incidences and severity of ischemic heart disease, but the mechanistic nature is unknown. Recently, we showed that regular exercise prolongs the left ventricular action potential duration (APD) at resting heart rate (HR) while shortening it at high HR. These adaptations enhance cardiac contractility at rest while preventing Ca 2þ overload and/or inadequate filling during exercise. Here we test the hypothesis that exercise-training induced changes in the APD are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
2
1

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…We have also recently observed similar non-AP-firing behaviours in a population of enzymatically isolated guinea pig and human SAN cells: these cells have LCRs but do not fire APs (36,37). A large population of these dormant isolated SAN cells begin to fire spontaneous APs in response to increases in intracellular cAMP (36,38). Such dormant cell behaviour within SAN tissue can potentially contribute to pacemaker function via (i) having a role in entrainment of oscillators that are heterogeneous 105 and is also made available for use under a CC0 license.…”
Section: Ca 2+ Signals Within Cells Embedded Within Hcn4 Meshwork Are Highly Heterogeneous In Spatial Distribution Amplitude Frequency Anmentioning
confidence: 56%
“…We have also recently observed similar non-AP-firing behaviours in a population of enzymatically isolated guinea pig and human SAN cells: these cells have LCRs but do not fire APs (36,37). A large population of these dormant isolated SAN cells begin to fire spontaneous APs in response to increases in intracellular cAMP (36,38). Such dormant cell behaviour within SAN tissue can potentially contribute to pacemaker function via (i) having a role in entrainment of oscillators that are heterogeneous 105 and is also made available for use under a CC0 license.…”
Section: Ca 2+ Signals Within Cells Embedded Within Hcn4 Meshwork Are Highly Heterogeneous In Spatial Distribution Amplitude Frequency Anmentioning
confidence: 56%
“…We have also recently observed similar non-AP-firing behaviours in a population of enzymatically isolated guinea pig and human SAN cells: these cells have LCRs but do not fire APs [34,35]. A large population of these dormant isolated SAN cells begin to fire spontaneous APs in response to increases in intracellular cAMP [34,36]. Such dormant cell behaviour within SAN tissue can potentially contribute to pacemaker function via (i) having a role in entrainment of oscillators that are heterogeneous both in phase and amplitude to self-organize into synchronized signals that underlie rhythmic impulse that emanate from the SAN; and (ii) their recruitment to fire APs in response to adrenergic receptor activation or AP silencing in response to cholinergic receptor stimulation.…”
Section: Some San Cells Have Lcrs But Do Not Fire Apsmentioning
confidence: 73%
“…1B). Next, SA node-residing atrial cells have a resting membrane potential between −70 and −80 mV [8], whereas our pilot measurements showed that dormant cells exhibit a resting membrane potential of about −35 mV [9]. In the presence of βAR stimulation, some dormant cells gained automaticity (Fig.…”
Section: Resultsmentioning
confidence: 99%